Regulation of Myeloid Progenitor Cell Proliferation/Survival by IL-31 Receptor and IL-31 - Broxmeyer, Hal E. (2007)
OBJECTIVE: IL-31 is a recently discovered helical cytokine. Its receptor consists of a ligand specific IL-31R subunit and a receptor chain that is shared with Oncostatin M (OSM), called OSM-Rβ. Because OSM-Rβ deficient animals have reduced hematopoietic progenitor cells (HPC) and OSM has effects on and is involved in homeostasis of HPC, we studied whether IL-31 and IL-31R play a role in hematopoiesis. METHODS: IL-31R(-/-) mice and their littermate WT controls were assessed for absolute numbers and cycling status of bone marrow and spleen HPC (CFU-GM, BFU-E, CFU-GEMM). Recombinant IL-31 was evaluated for stimulation, enhancement, or inhibition of colony formation by HPC, and for survival enhancing effects on HPC subjected to growth factor withdrawal and delayed addition of grown factors. Hematopoietic stem cells (HSC) from WT and IL-31R(-/-) mice were compared for competitive repopulating capacity in lethally irradiated congenic mice. RESULTS: IL-31R(-/-) mice demonstrated significantly decreased absolute numbers and cycling status of immature subsets of HPC in bone marrow bone and spleen compared to WT mice. There were no significant differences in absolute numbers of more mature subsets of WT and IL-31R(-/-) bone marrow CFU-GM. WT but not IL-31R(-/-) bone marrow CFU-GM responded to synergistic stimulation by combinations of cytokines. While IL-31 had neither colony stimulating, enhancing, or inhibiting activity for bone marrow HPC, it did enhance survival of these HPC in the context of delayed addition of growth factors. No significant differences were detected in competitive repopulating HSC activity between WT and IL-31R(-/-) bone marrow cells. CONCLUSIONS: IL-31R is involved in positive regulation of absolute numbers and cycling status of immature subsets of HPC in vivo. While IL-31 in vitro does not modulate proliferation of HPC, it does enhance their survival, which may contribute to effects on cycling and numbers of HPC in vivo. Under steady state conditions, loss of IL-31R on HPC does not appear to influence the activity of competitive repopulating HSC. These results with HPC may be of future utility for manipulation of hematopoiesis in a pre-clinical setting.